Analisis Sistem Margin Keuntungan Pada PembiayaanBai' Bi Ṡaman Ajil Di BMT Dirgantara Pasar Kliwon Surakarta - Ulvi, Rukaya; , Dr. M. Muhtarom, SH. MH (2016)
The study aims to determine the mechanism for the results of the financing system Bai' Bi ṠamanAjil at BMT Dirgantara Pasar Kliwon Surakarta and knowing the constraints in the implementation of the system for financing the results of the Bi Bai' Ṡaman Ajil at BMT Dirgantara Pasar Kliwon Surakarta. This research is a qualitative approach and descriptive. This research is a qualitative descriptive study. This research was conducted by direct observation at BMT Dirgantara Pasar Kliwon Surakarta. The research subjects were Leaders and Employees BMT Dirgantara Pasar Kliwon Surakarta. Methods of data collection in studies using interviews, observation, and documentation. This research uses descriptive data analysis, namely data obtained is then poured in the form of words or pictures, then described so as to provide clarity fact realistic. Based on the survey results revealed that mekaniseme revenue sharing system on the financing of Bai' Bi Ṡaman Ajil at BMT DirgantaraPasarKliwon Surakarta are as follows: (1) There is an agreement between the parties BMT Dirgantara Pasar Kliwon Surakarta (şahibul maal) with a money management; (2) The client gives his business certificates as collateral at BMT Dirgantara Pasar Kliwon Surakarta; (3) System for the results conducted by the TMB in accordance with the going concern which the customer must be able to meet its obligations in the payment of principal; (4) Ratio imposed by clients to one another can be different even though the same type of business;. Constraints faced is the low number of human resources, lack of public understanding about the concept of profit sharing and control of the management of funds for entrepreneurs. The solution is to provide guidance to members gradually and guidance directly in business book keeping. Keywords: profit-margin, bai' bi ṡamanajil, financing